1. The problem statement, all variables and given/known data y'' + ty' - y = 0 plugging in the known Laplace formuals i get this.... [s^2Y(s) - sy(0) - y'(0)] + [-sY'(s) - Y(s)] - Y(s) = 0 2. Relevant equations y(0) = 0 y'(0) = 3 3. The attempt at a solution simplying to a linear first order DE -sY'(s) + (s^2-2)Y(s) = 3 Y'(s) + [(s^2-2)/-s]Y(s) = 3 now, according to my text book "P(x)" = [(s^2-2)/-s], and i need to find the integrating factor by integrating P(x) use e^(p(x)) then etc. the problem im having is how to approach integrating p(x). i tried dividing each term by s and integrating them separately but plugging them into e causes hectic problems. is there a different way to approach this?